Kesantunan Berbahasa Calon Legislatif dalam Podcast Tribun Timur.com: The Politeness of Legislative Candidates in the Tribun Timur.com Podcast - Nurhaliza, Andi Siti; Usman, Usman; Fitri, Sakinah (Journal Studies in Indonesian Language and Literature, 2025)
The general purpose of this study is to analyze the politeness of language of legislative candidates in podcasts on Tribun Timur.com. The data collection method used is a qualitative description method. Qualitative research generally adopts a case study design that focuses on a particular phenomenon to be understood while other phenomena are ignored. The results of this study indicate that the politeness of language of legislative candidates in the Tribun Timur.com podcast more often adheres to maxims, especially in terms of generosity, wisdom, and agreement. Based on the analysis of the data found, it can be concluded that the politeness of language of legislative candidates in the Tribun Timur.com podcast adheres to maxims more than those who do not, especially in terms of generosity, wisdom, and agreement.